2008
DOI: 10.1073/pnas.0801692105
|View full text |Cite
|
Sign up to set email alerts
|

RNA landscape of evolution for optimal exon and intron discrimination

Abstract: Accurate pre-mRNA splicing requires primary splicing signals, including the splice sites, a polypyrimidine tract, and a branch site, other splicing-regulatory elements (SREs). The SREs include exonic splicing enhancers (ESEs), exonic splicing silencers (ESSs), intronic splicing enhancers (ISEs), and intronic splicing silencers (ISSs), which are typically located near the splice sites. However, it is unclear to what extent splicing-driven selective pressure constrains exonic and intronic sequences, especially t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
111
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(113 citation statements)
references
References 32 publications
1
111
0
1
Order By: Relevance
“…S4b). These 150-base intronic regions were shown to contain regulatory sequences for splicing (Wang and Burge 2008;Zhang et al 2008a;Woolfe et al 2010).…”
Section: Collection Of Editing Sitesmentioning
confidence: 99%
“…S4b). These 150-base intronic regions were shown to contain regulatory sequences for splicing (Wang and Burge 2008;Zhang et al 2008a;Woolfe et al 2010).…”
Section: Collection Of Editing Sitesmentioning
confidence: 99%
“…Each utility perform a local search of the exonic sequence for putative ESEs/PESSs (PESEs/PESSs) [Zhang and Chasin, 2004], FAS-ESSs [Wang et al, 2004], RESCUEESEs [Fairbrother et al, 2002;Fairbrother et al, 2004], neighbourhood inference [Stadler et al, 2006] and exon/intron identity elements (EIE/IIEs) [Zhang et al, 2008] The performance of HOT-SKIP was tested with a set of 37 previously reported mutations that resulted in exon skipping and genetic disease (Supplementary Table 4). …”
Section: Ex-skip and Hot-skip Constructionmentioning
confidence: 99%
“…To determine which of the previously determined ESSs or ESEs correlate best with exon inclusion levels, the number of RESCUE-ESEs [Fairbrother et al, 2002;Fairbrother et al, 2004], FASS-ESSs [Wang et al, 2004], PESEs/PESSs [Zhang and Chasin, 2004], neighbourhood inference elements [Stadler et al, 2006] and EIE/IIEs [Zhang et al, 2008] was calculated for each segment. In addition, we employed the ESEfinder [Cartegni et al, 2003;Smith et al, 2006] to correlate exon inclusion levels with predicted scores of putative ESEs for SR proteins.…”
Section: Correlation Of the Ess/ese Profile And Exon Inclusionmentioning
confidence: 99%
“…For example, selection may act to reduce crossovers within genes if recombination is mutagenic (McVean et al 2004) and could result in strand-biased composition for efficient splicing (Zhang et al 2008). Selection could also explain the enrichment of Alus near genes of specific functional categories if selection against transposable elements is weaker for these genes (Grover et al 2003) or if selection promotes the fixation of Alus with regulatory potential (Tsirigos and Rigoutsos 2009).…”
mentioning
confidence: 99%